2015
DOI: 10.1163/18759866-08402004
|View full text |Cite
|
Sign up to set email alerts
|

The anatomy of the king crab Hapalogaster mertensii Brandt, 1850 (Anomura: Paguroidea: Hapalogastridae) – new insights into the evolutionary transformation of hermit crabs into king crabs

Abstract: The emergence of king crabs from a hermit crab-like ancestor is one of the most curious events in decapod evolution. King crabs comprise two taxa, Lithodidae and Hapalogastridae, and while lithodids have formed the focus of various anatomical studies, the internal anatomy of hapalogastrids has never been studied although this group might represent a more ancestral morphological condition within king crabs than lithodids do. To better understand the evolutionary transformation of pagurid-like hermit crabs into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…• Xradia MicroXCT-200 X-ray imaging system (Carl Zeiss X-ray Microscopy Inc., Pleasanton, USA). For detailed parameters and details of the process see Keiler et al (2015b).…”
Section: Microcomputer Tomography (Microct)mentioning
confidence: 99%
See 1 more Smart Citation
“…• Xradia MicroXCT-200 X-ray imaging system (Carl Zeiss X-ray Microscopy Inc., Pleasanton, USA). For detailed parameters and details of the process see Keiler et al (2015b).…”
Section: Microcomputer Tomography (Microct)mentioning
confidence: 99%
“…provide evidence of sister group relationships (Keiler et al, 2013(Keiler et al, , 2015a, and at the same time shed light on the morphological transformations which took place in the course of carcinization. Studies into king crabs (Keiler et al, 2013(Keiler et al, , 2015b and porcelain crabs (Keiler et al, 2015a) have shown that carcinization in these two lineages was characterized by similar changes in external morphology, e.g. the pleon became flexed and started to be carried tightly under the cephalothorax, which led to the concave emargination of the posterior margin of the sternal plastron and the broadening of the carapace.…”
Section: Introductionmentioning
confidence: 99%
“…However, pagurid hermit crab asymmetries, influenced by inhabiting dextral gastropod shells (Palmer, 2004), such as pleon and claw asymmetries (McLaughlin & Lemaitre, 1997, 2000McLaughlin et al, 2004;Duguid, 2010), are still present in lithodids (Tsang et al, 2011). Further traces of their pagurid origin can, for example, be found in the mouthparts (Boas, 1924;Jaszkowiak et al, 2015), setation (Keiler & Richter, 2011), internal organ organization (Anker & Paulay, 2013;Keiler et al, 2015) or vascular system (Keiler, Richter & Wirkner, 2013;Keiler et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…No previous work has ever addressed the functional mouthpart morphology of Lithodidae which is particularly interesting in the framework of carcinization, the evolutionary transformation into a crab‐like habitus (Keiler et al . , ). Although recent studies have shown striking differences between the branching pattern of the arteries supplying the mouthparts in Lithodidae and Paguridae (Keiler et al .…”
Section: Introductionmentioning
confidence: 99%
“…We also refer to Keiler et al . (, ) for a detailed discussion of phylogenetic relationships of king crabs. Following the approach suggested by Garm and Høeg (), this study aims to fill this gap and to compare the information on functional morphology and functional groups in L. maja (Linnaeus, 1758) gained herein with that available for Munida sarsi (Huus, 1935) and Munida tenuimana (G.O.…”
Section: Introductionmentioning
confidence: 99%